Everyday Racism in Integrated Spaces: Mapping the Experiences of Students of Color at a Diversifying Predominantly White Institution. Issue 5 (3rd September 2018) - Harwood, Stacy Anne; Mendenhall, Ruby; Lee, Sang S.; Riopelle, Cameron; Huntt, Margaret Browne
Abstract : Many college campuses promote themselves as integrated multicultural spaces where students from diverse backgrounds live, study, and play together in unity. Drawing from eleven focus groups and an online survey with more than 4, 800 students of color, this study reveals that many students of color experience racial hostility and exclusion in their daily routines. Using the concept of racial microaggressions, we expand the definition of racism to identify three representational spaces that reflect the lived experiences of students of color at a predominantly white institution: (1) fortified, a space of white dominance where students of color often experience explicit racism; (2) contradictory, a space of covert racial dominance where students of color regularly experience being treated as second-class citizens; and (3) counter, a space created as an act of resistance or survival for students of color but one that also faces opposition. This study demonstrates that the inclusive, racially harmonious multicultural campus is an imaginary geography.